Functional analysis of the dehydratase domains of the PUFA synthase from Emiliania huxleyi in Escherichia coli and Arabidopsis thaliana - Bihan Chen; Feng Wang; Xi Xie; Huifan Liu; Dongjie Liu; Lukai Ma; Gengsheng Xiao; Qin Wang (Biotechnology for Biofuels and Bioproducts, 2022)
Abstract Background Polyunsaturated fatty acid (PUFA) synthase is a multi-domain mega-enzyme that effectively synthesizes a series of PUFAs in marine microorganisms. The dehydratase (DH) domain of a PUFA synthase plays a crucial role in double bond positioning in fatty acids. Sequencing results of the coccolithophore Emiliania huxleyi (E. huxleyi, Eh) indicated that this species contains a PUFA synthase with multiple DH domains. Therefore, the current study, sought to define the functions of these DH domains (EhDHs), by cloning and overexpressing the genes encoding FabA-like EhDHs in Escherichia coli (E. coli) and Arabidopsis thaliana (A. thaliana). Results A complementation test showed that the two FabA-like DH domains could restore DH function in a temperature-sensitive (Ts) mutant. Meanwhile, overexpression of FabA-like EhDH1 and EhDH2 domains increased the production of unsaturated fatty acids (UFAs) in recombinant E. coli by 43.5–32.9%, respectively. Site-directed mutagenesis analysis confirmed the authenticity of active-site residues in these domains. Moreover, the expression of tandem EhDH1-DH2 in A. thaliana altered the fatty acids content, seed weight, and germination rate. Conclusions The two FabA-like DH domains in the E. huxleyi PUFA synthase function as 3-hydroxyacyl-acyl carrier protein dehydratase in E. coli. The expression of these domains in E. coli and A. thaliana can alter the fatty acid profile in E. coli and increase the seed lipid content and germination rate in A. thaliana. Hence, introduction of DH domains controlling the dehydration process of fatty acid biosynthesis in plants might offer a new strategy to increase oil production in oilseed plants.